Carcinogens can induce homologous recombination between duplicated chromosomal sequences in mouse L cells. - Wang, Y Y (1988)
The ability of a series of DNA-damaging agents to induce homologous intrachromosomal recombination between duplicated genes in the chromosome of mouse cells was investigated. The target cells were the thymidine kinase-deficient mouse L-cell strain 333M, which contains a single integrated copy of a plasmid with two herpes simplex virus thymidine kinase (Htk) genes, each containing an 8-base-pair XhoI linker inserted at a unique site. Expression of a functional Htk enzyme requires a productive recombinational event between the two nonfunctional genes. The spontaneous rate of recombination in this strain is 3 per 10(6) cells per generation. The agents tested represent physical carcinogens (UV and ionizing radiation), a simple alkylating agent (N-methyl-N'-nitro-N-nitrosoguanidine), an alkylating cross-linking agent (mitomycin C), and a reactive metabolite of a polycyclic aromatic hydrocarbon ((+/-)-7 beta,8 alpha-dihydroxy-9 alpha,10 alpha-epoxy-7,8,9,10- tetrahydrobenzo[a]pyrene [BPDE] ). The background frequency of tk+ recombinants in the untreated population averaged 18 X 10(-6) +/- 5 X 10(-6). Ionizing radiation had little or no effect on recombination; exposure to mitomycin C, N-methyl-N'-nitro-N-nitrosoguanidine, BPDE, or UV, at doses that lowered the survival to between 90 and 10% of the control, caused a dose-dependent increase in frequency of recombinants, reaching 50 X 10(-6) to 100 X 10(-6). No tk+ cells could be generated with a control cell line that contained only one mutant copy of the Htk gene. Molecular hybridization analysis showed that 85 to 90% of the tk+ recombinants retained the Htk gene duplication, consistent with nonreciprocal transfer of wild-type genetic information, gene conversion. In the rest, only a single copy of the Htk gene remained, reflecting a single reciprocal exchange within a chromatid or a single unequal exchange between sister chromatids. Each recombinant tested contained an XhoI-resistant (wild-type) Htk gene.